Characteristics, controlling factors of development and exploration areas of deep coal-rock reservoirs in rift basins: a case study of the second member of Cretaceous Nantun Formation in Huhehu Sag, Hailar Basin - Geng GAO; Yingyi XIE; Beibei HOU; Wenjuan MA; Hui XU; Yujie WANG; Yingdong HUO; Jingyuan ZHANG; Shichao LIU; Wei ZHAO; Yuan LIANG (Shiyou shiyan dizhi, 2025)
In recent years, major breakthroughs have been made in deep coal-rock gas exploration, revealing the promising exploration prospects of such resources. This has become a new hotspot in unconventional oil and gas exploration and development, following tight oil and gas and shale oil and gas. The second member of Cretaceous Nantun Formation (N2) in the Huhehu Sag of Hailar Basin is characterized by deep coal-rock layers in a thick stack with high resource potential for deep coal-rock gas. This region is an important area for exploration succession. Clarifying the characteristics, main controlling factors, and development patterns of deep coal-rock reservoirs is essential for the exploration and development of deep coal-rock gas in the coal-bearing rift basins of northeastern China. Based on drilling and seismic data from the Huhehu Sag, the characteristics and main controlling factors of the high-quality coal rock reservoirs in N2 are studied through core and thin section observations and experimental analysis. The coal-rock reservoirs in N2 of the Huhehu Sag have the characteristics of low ash content, ultra-low moisture content, and medium to high volatile matter. The main reservoir space is mainly composed of organic pores, fractures, and inorganic mineral pores, with porosity mainly distributed between 4.5% to 7.6%, with an average of 6.0%. The average permeability is 0.45×10-3 μm2, and the pore structure is mainly microporous, with a high proportion of macropores, making it easier for free gas storage. Swampy shore-shallow lakes are widely distributed, controlling the large-scale development of coal rocks, providing material sources and storage space for deep coal-rock gas reservoir formation. High-quality coal-rock reservoirs are mainly developed in the depression zones and steep slope zones, where swampy shore and shallow lakes are widely distributed. The coal-rocks formed in these areas are mainly bright to semi-bright primary structural coal, forming cleats, organic pores, and micro-fractures. Organic pores are connected to micro-fractures, resulting in high pore connectivity, better physical properties, superior gas content, and richer "free gas". The southern depression zones and steep slope zones are more likely to form multiple favorable source and reservoir configurations, with superior reservoir formation conditions. The predicted resource volume exceeds one trillion cubic meters, making it a favorable breakthrough area for deep coal-rock gas exploration in the Huhehu Sag. It is expected to become the first trillion-cubic-meter deep coal-rock gas field in the Hailar Basin.